2018
DOI: 10.1021/acs.jpca.7b11774
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Low to High Iodide and Iodine Concentration States in the Briggs–Rauscher Reaction: Evidence on Crazy Clock Behavior

Abstract: The Briggs-Rauscher reaction containing malonic acid may undergo a sudden transition from low (state I) to high iodide and iodine (state II) concentration states after a well-defined and strongly reproducible oscillatory period. This study clearly shows that even though the time-dependent behavior of the oscillatory state is reproducible, the time lag necessary for the appearance of the state I to state II transition after the system leaves the oscillatory state becomes irreproducible for an individual kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…This expectation, along with the fact that the arsenous acid-iodate reaction exhibits crazy-clock behavior (CCB) as reported recently by our research group, 11 has led us to elucidate the comprehensive kinetic model of the arsenous acid-iodate system, 12,13 including the well-known Dushman 14 and Roebuck 15 reactions. Very recently, Pagnacco et al reported 16 that the state I (low iodide and iodine concentration) to state II (high iodide and iodine concentration) transition of the Briggs-Rauscher reaction 17 after leaving the strongly reproducible oscillatory state was found to be irreproducible as well. Moreover, an efficient mixing does not only prolong the time lag necessary for the state I to state II transition, it simply does not allow it to happen.…”
Section: Introductionmentioning
confidence: 99%
“…This expectation, along with the fact that the arsenous acid-iodate reaction exhibits crazy-clock behavior (CCB) as reported recently by our research group, 11 has led us to elucidate the comprehensive kinetic model of the arsenous acid-iodate system, 12,13 including the well-known Dushman 14 and Roebuck 15 reactions. Very recently, Pagnacco et al reported 16 that the state I (low iodide and iodine concentration) to state II (high iodide and iodine concentration) transition of the Briggs-Rauscher reaction 17 after leaving the strongly reproducible oscillatory state was found to be irreproducible as well. Moreover, an efficient mixing does not only prolong the time lag necessary for the state I to state II transition, it simply does not allow it to happen.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as described elsewhere [16], after the well-controlled initial oscillatory behavior, the reaction becomes chaotic. Depending on the initial conditions, particularly on the ratio [H 2 MA] 0 /[IO 3 − ] 0 [16,17], the reaction exhibits a sudden and unpredictable phase transition.…”
Section: Introductionmentioning
confidence: 70%
“…Indeed, as described elsewhere [16], after the well-controlled initial oscillatory behavior, the reaction becomes chaotic. Depending on the initial conditions, particularly on the ratio [H 2 MA] 0 /[IO 3 − ] 0 [16,17], the reaction exhibits a sudden and unpredictable phase transition. This transition, from state I (low concentration of iodide and iodine) to state II (high concentration of iodide and iodine), happens randomly in practice, as the time spent by the system in the state I is irreproducible (see Figure 1).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations